2004
DOI: 10.3171/jns.2004.101.2.0303
|View full text |Cite
|
Sign up to set email alerts
|

Blood—brain barrier opened by stimulation of the parasympathetic sphenopalatine ganglion: a new method for macromolecule delivery to the brain

Abstract: Sphenopalatine ganglion activation demonstrates a promising potential for clinical use in the delivery of small and large molecules to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…For example, studies have shown that loss of direct noradrenergic input from the locus coeruleus results in increased BBB susceptibility to effects of acute hypertension, resulting in significantly increased permeability to 125 -I labeled albumin (57). Additionally, stimulation of the parasympathetic sphenopalatine ganglion has been found to induce BBB opening resulting in an increase in delivery of chemotherapeutic agents (i.e., anti-HER2 monoclonal antibody, etoposide) to the brain (72). In contrast, in a rodent model of traumatic brain injury (TBI), vagal stimulation following TBI resulted in a decrease in BBB permeability to FITC-dextran as compared to animals with TBI alone (73).…”
Section: Components Of the Nvumentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have shown that loss of direct noradrenergic input from the locus coeruleus results in increased BBB susceptibility to effects of acute hypertension, resulting in significantly increased permeability to 125 -I labeled albumin (57). Additionally, stimulation of the parasympathetic sphenopalatine ganglion has been found to induce BBB opening resulting in an increase in delivery of chemotherapeutic agents (i.e., anti-HER2 monoclonal antibody, etoposide) to the brain (72). In contrast, in a rodent model of traumatic brain injury (TBI), vagal stimulation following TBI resulted in a decrease in BBB permeability to FITC-dextran as compared to animals with TBI alone (73).…”
Section: Components Of the Nvumentioning
confidence: 99%
“…For example, electrical stimulation of postganglionic parasympathetic fibers of the sphenopalatine ganglion (SPG) has been shown to increase BBB permeability to FITC-dextran, implying an increase in BBB permeability (72). Delivery of etoposide and HER2 monoclonal, both chemotherapeutic agents, was also improved by the use of electrical stimulation of postganglionic parasympathetic fibers of the SPG (72). Stimulation of the SPG has also been found to induce reperfusion and BBB protection in a rodent stroke model (362).…”
Section: Blood-brain Barrier Opening Via Ultrasound and Electrical Stmentioning
confidence: 99%
“…The authors attributed this to a compensatory mechanism in order to maintain a constant supply of nutrients to the brain during variations in cerebral blood flow. Yarnitsky et al, 2004 showed that stimulation of parasympathetic nerve fibers arising from the sphenopalatine ganglion, resulted in a reversible increase in BBB permeability, with enhanced entry of macromolecules such as FITC-dextran, Evans blue dye-albumin and the chemotherapeutic agents anti-HER2 mAb and etoposide into the brain. Using a neuropathic pain model of peripheral chronic nerve lesion, Gordh and Sharma, 2006, demonstrated a loss of blood-spinal cord barrier integrity, with increased permeability and activation of astrocytes in the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Parasympathetic innervation from the PPG acting directly or indirectly on nociceptive sensory fibres has also been suggested to participate in regulation of blood–brain barrier (BBB) permeability (Delépine & Aubineau, ; Yarnitsky et al . a , b ) and development of cluster headaches/migraine (Yarnitsky et al . ).…”
Section: Other Proposed Functions Of Parasympathetic Innervation To Cmentioning
confidence: 99%
“…This effect of PPG stimulation has been used clinically to deliver macromolecules through the BBB (Yarnitsky et al . a ). Hence the (over‐) stimulation of the parasympathetic innervation to the cerebral arteries may not only yield positive effects.…”
Section: Parasympathetic Targets With Clinical Relevance For the Cerementioning
confidence: 99%